Evaluating the Effectiveness of the BAAS Program in Reducing Stunting in Takalar Regency - Damayati, Dwi Santy; Azriful, Azriful; Sumarlin, Rudi (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: The complexity of stunting reduction interventions cannot be addressed by the government alone. The state appreciates contributions from all stakeholders, including the community. The Foster Parents for Stunting Children (BAAS) program provides a platform for stakeholder participation in accelerating stunting reduction. As a relatively new program, a review is needed to assess its impact. This study aims to evaluate the effectiveness of the BAAS program in Takalar Regency in 2023. Methods: This study uses quantitative research with a cross-sectional approach. Data analysis was conducted to determine how much the success measure of the BAAS program based on the target approach (output). In this study, the test used was the Wilcoxon signed rank test to see the impact (outcome) of how significant the program was to reduce the prevalence of stunting. Results: There is a statistically significant difference between the Z-score TB/U and BB/U before and after the BAAS program with a mean Z-score TB/U before the program of -2.78 and BB/U of -1.83 and a mean Z-score TB/U after the program of -0.40 and BB/U of -0.91. Based on the p-value of Z-score TB/U and BB/U showed a very small value for Z-score TB/U of 0.000 (<0.05). and BB/U of <0.001. This suggests that the program is effective for improving nutritional status and can reduce stunting and wasting in Takalar District. Conclusion: The BAAS Program successfully demonstrated its effectiveness in improving the nutritional status of children in Takalar District. The Wilcoxon Signed Rank Test results also showed a statistically significant difference between the Z-score values before and after the program with a p value <0.05, confirming that the BAAS Program is effective in improving nutrition and reducing stunting in Takalar District. BAAS is an effective intervention model with the potential for replication and expansion, serving as a reference for sustainable and inclusive community-based stunting prevention policies.